Liberalisation of Environmental Goods & Services and Climate Change - Patricia Iturregui; Michael Dutschke (Hamburg Institute of International Economics (HWWA), 2005)
This paper attempts to show how WTO negotiations on liberalisation of environmental goods and services can have a negative or positive impact on the international climate change policy depending on the outcome of the Doha Mandate paragraph 31 debates. Certainly there has been no significant progress on the definition or classification of environmental goods and services given the wide spectrum of positions. However, the size of the environmental market is not little and a pragmatic approach for negotiations can be to reduce the issue by parts in problem areas being one of them air pollution and climate. In order to succeed in the task some conditions must be achieved, namely balancing interests from OECD and non OECD countries, identification of a list of key goods and services, tackling barriers to trade and avoiding ?pollution transfer?
Keywords: 330; WTO and UNFCCC; liberalization of environmental goods and services; air pollution and climate; Umweltschutzsektor; Außenhandelsliberalisierung; Klimaschutz; Welt